PELATIHAN INOVASI TENUN MELALUI DESAIN DIGITAL UNTUK PENINGKATAN KUALITAS TENUN PADA SONGKET BERKAH NAGARI SUNGAI JANIAH KABUPATEN SOLOK - Ratni Prima Lita; Sanda Patrisia Komalasari; Budi Rahmadya; Yanti Yanti; Rida Rahim; Suziana Suziana; Eri Besra; Laura Amelia Triani; Rita Rahayu; Verinita Verinita; Rahmi Fahmy; Vera Pujani; et al. (Jurnal Hilirisasi IPTEKS)
This community service activity aims to enhance the quality and innovation of Tenun Songket Berkah designs in Nagari Sungai Janiah, Solok Regency, through digital design training using Adobe Illustrator. The program was held on July 27, 2024, at the Tenun Songket Berkah micro-enterprise, employing various methods such as training, hands-on practice, and mentoring. The primary goal of this activity is to introduce digital design techniques that can develop traditional tenun motifs to be more innovative, modern, and appealing to both local and international markets. The implementation methods included intensive training on the use of Adobe Illustrator, practical sessions on creating digital-based tenun motifs, and ongoing mentoring to develop unique and creative designs. Participants were trained to optimize the use of this software to create complex and detailed motifs, which were then integrated into the production process. The results of the activity showed a significant improvement in the participants' ability to use Adobe Illustrator for designing tenun motifs, positively impacting the quality, variety, and added value of the products. A total of 10 new motifs were successfully created, marketed, and registered as Intellectual Property Rights (IPR), strengthening the position of the micro-enterprise in the market. In conclusion, this training proved effective in fostering innovation in the Tenun Songket Berkah industry, enhancing human resource skills, and expanding the market reach. It is recommended to continue with advanced training in product design and digital marketing to maintain and enhance the competitiveness of the products in the global market.